1913: Annus Mirabilis of Esophageal Surgery - Kun, Levente; Herbella, Fernando A.; Dubecz, Attila (The Thoracic and Cardiovascular Surgeon, 2013)
Although Sir Ronald Belsey once called the year 1904 “annus mirabilis,” it is actually the year 1913 that stands out as the true milestone in esophageal surgery. Within a year, Torek performed the first transpleural resection for cancer in the thoracic esophagus, Zaaijer successfully resected the distal esophagus through the transpleural route, Heller performed the first myotomy for achalasia, and it was also the year of Ach's pioneering transmediastinal esophagectomy. Previously, in 1912, after a series of animal experiments by Beck and Jianu, Roepke successfully used the greater curvature of the stomach as a presternal conduit. Other previous approaches included reconstruction with jejunum (Roux—1907), colon (Kelling—1911), and skin tube (Bircher—1907). Several technical advances made these operations possible, most of all were the giant leaps in the perioperative medicine.
Keywords: esophageal surgery; historical article; thoracic surgery